A copper-based three-dimensional self-supporting electrode material, a preparation method therefor and applications thereof
Patent Information
- Application Number
- CN202311401164.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-10-26
AI Technical Summary
然而,尽管含贵金属的单质或化合物被报道为高性能催化剂,贵金属的昂贵价格与稀少的储量限制了材料的大批量制备与技术的大规模应用
(1)如今贵金属市场价格高昂导致其应用成本高,不利于材料的推广和规模化应用。本发明针对电催化硝酸盐制氨领域的高性能催化剂过度依赖于贵金属催化剂问题,使用常规的过渡金属(Cu)为原材料制备得到了高性能催化剂。本发明的非贵金属三维电极材料,具有丰富的金属活性位点,表现出优异的表界面吸附特性,以及不逊色于贵金属的催化活性,为电催化硝酸盐制氨技术大规模应用的成本降低提供了可能。
Smart Images

Figure CN117626308B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalytic materials technology, specifically relating to a copper-based three-dimensional self-supporting electrode material, its preparation method, and its application. Background Technology
[0002] Ammonia is one of the most widely produced chemicals in human life and industry. It plays a vital role not only in the manufacture of agricultural fertilizers and industrial products, but is also considered a next-generation energy carrier due to its high energy density (4.3 kWh / kg) and pollution-free nature. Currently, the ammonia production industry heavily relies on the high-temperature, high-pressure Haber process, consuming approximately 1-2% of the world's energy annually and emitting over 420 million tons of greenhouse gas equivalent. Therefore, under the dual-carbon vision, a new ammonia production solution with low energy consumption and low emissions is urgently needed.
[0003] For the past decade, the electrocatalytic reduction of nitrogen to produce NH3 using water as a hydrogen source has been an interesting topic. However, due to the high dissociation energy of the N≡N bond (941 kJ / mol) and the competitive hydrogen evolution reaction (HER), the Faraday efficiency (FE) of NH3 is low. Therefore, there is an urgent need to explore new pathways for green NH3 synthesis under favorable conditions. On the other hand, nitrate pollution in groundwater is a widespread problem worldwide. Physicochemical methods such as electrodialysis, ion exchange, and reverse osmosis have been used to treat or remove nitrate pollution from wastewater. However, since these physicochemical processes can only separate and concentrate nitrates, but not completely destroy them, they often require expensive post-treatment processes, which may generate large amounts of secondary brine waste. From the perspective of turning waste into treasure, converting nitrate pollution in wastewater into recyclable ammonia is a highly attractive environmental strategy.
[0004] The electrochemical reduction of nitrate to ammonia is limited by competitive HER and 8-electron-9-proton complexation reduction. Therefore, developing efficient electrocatalysts is essential for the application of electrochemical nitrate to ammonia technology. Copper-based materials possess unique advantages in the selective electrocatalytic reduction of nitrate to ammonia. To improve electrocatalyst performance, extensive research has been conducted on the active sites, including precise optimization of the morphology and structure of electrocatalysts and adjustment of their composition. Among various nanostructures, one-dimensional nanowire arrays have proven advantageous in electrocatalysis due to their abundant, exposed active sites and efficient charge transfer. Furthermore, surface modification of heterogeneous electrocatalysts, particularly using organic molecules or polymers, has become an effective approach to enhance their electrocatalytic activity. For example, polyethyleneimine (PEI)-functionalized Au nanowires@Pd core-shell bimetallic nanohybrids (Au-NWs@Pd@PEI) exhibit excellent electrocatalytic performance for the oxygen reduction reaction due to the -NH2 functional group of PEI. Tannic acid (TA) complexed with different metal ions also exhibits excellent electrocatalytic performance due to the synergistic effect between the composite coatings, achieving good surface property tuning. Despite these advances, few studies to date have focused on the selective electroreduction of nitrate to ammonia through surface molecule or polymer functionalization.
[0005] The document DOI number is 10.1021 / acscatal.8b03447, and the title is "Au Nanowires@Pd-Polyethylenimine Nanohybrids as Highly Active and Methanol-Tolerant Electrocatalysts toward Oxygen Reduction Reaction in Alkaline Media". This invention relates to the preparation and application of electrocatalytic reduction electrode materials functionalized with small organic molecules, exhibiting excellent performance during the reduction process. However, although elements or compounds containing noble metals have been reported as high-performance catalysts, the high price and limited reserves of noble metals restrict the large-scale preparation of these materials and the large-scale application of the technology. Therefore, the development and design of non-noble metal catalysts with high activity and stability is of great practical significance. Summary of the Invention
[0006] In order to overcome the shortcomings of the existing technology, the purpose of this invention is to provide a method for preparing and applying a copper-based three-dimensional self-supporting electrode material for organic surface modification in the production of ammonia by nitrate reduction.
[0007] The primary objective of this invention is to propose a method for preparing a three-dimensional self-supporting electrode material with organic surface modification.
[0008] Another object of the present invention is to provide a three-dimensional self-supporting electrode material with the above-mentioned organic surface modification.
[0009] Another object of the present invention is to provide the application of the three-dimensional self-supporting electrode material based on the above-mentioned organic surface modification in the electrocatalytic reduction of nitrate to ammonia.
[0010] The objective of this invention is achieved by at least one of the following technical solutions.
[0011] A method for preparing a copper-based three-dimensional self-supporting electrode material includes the following steps: (1) Using conductive three-dimensional substrate copper foam as the anode, positive voltage was applied in sodium hydroxide solution for electro-oxidation to obtain Cu(OH)2 nanoneedle array precursor electrode material; (2) The Cu(OH)2 nanoneedle array precursor electrode material obtained in step (1) is thoroughly immersed in pure water and then dried. It is then annealed in an inert gas atmosphere to dehydrate the precursor electrode material and obtain a precursor covered by copper oxide nanoneedle array. (3) Using the precursor covered by the copper oxide nanoneedle array obtained in step (2) as the anode, positive voltage electropolymerization is applied in a mixed solution of aniline and sodium sulfate. After immersion in pure water and drying, a copper-based three-dimensional self-supporting electrode material modified with polyaniline (PANI) surface is obtained.
[0012] Further, the concentration of the sodium hydroxide solution in step (1) is 3~8 mol / L.
[0013] Further, the temperature of the electro-oxidation in step (1) is 25~50℃; the time of the electro-oxidation is 300~1800s.
[0014] Furthermore, in step (1), the electro-oxidation uses a platinum mesh as the cathode and Ag / AgCl as the reference electrode.
[0015] Further, the electro-oxidation in step (1) is performed in a constant current mode, wherein the anolyte current density in the constant current mode is 15~45 mA·cm. -2 .
[0016] Preferably, the current density of the electro-oxidation in step (1) is 40 mA·cm⁻¹. -2 (vs. Ag / AgCl), the electro-oxidation time is 600s.
[0017] Further, the annealing in step (2) is carried out in a tube furnace; before the annealing, an inert gas needs to be introduced for 30 minutes, the annealing temperature is 250~350℃, the annealing heating rate is 2℃ / min, and the annealing time is 100~120min; the inert gas is argon.
[0018] Preferably, the annealing temperature in step (2) is 300°C and the annealing time is 120 min.
[0019] Further, in step (3), the concentration of aniline in the mixed solution is 0.01~0.02 mol / L, and the concentration of sodium sulfate is 0.05~0.1 mol / L.
[0020] Preferably, the concentration of aniline in the mixed solution in step (3) is 0.01 mol / L and the concentration of sodium sulfate is 0.05 mol / L.
[0021] Further, the electropolymerization temperature in step (3) is 25~50℃; the electropolymerization time is 300~800s.
[0022] Furthermore, in step (3), the electropolymerization uses a platinum mesh as the cathode and Ag / AgCl as the reference electrode.
[0023] Further, the electropolymerization in step (3) is performed in a constant current mode, wherein the anolyte current density in the constant current mode is 0.5~0.8 mA·cm. -2 .
[0024] Preferably, the current density of the electropolymerization in step (3) is 0.5 mA·cm⁻¹. -2 (vs. Ag / AgCl), electropolymerization time was 500s.
[0025] The copper-based three-dimensional self-supporting electrode material prepared by any of the above preparation methods.
[0026] The present invention also provides the application of the above-mentioned copper-based three-dimensional self-supporting electrode material in the electrocatalytic nitrate reduction reaction.
[0027] Furthermore, the application uses a three-dimensional self-supporting electrode material as the working electrode and a solution containing nitrate ions as the electrolyte to carry out an electrocatalytic nitrate reduction reaction to synthesize ammonia; the reactor is designed as a three-chamber reactor, consisting of an acid capture chamber, an anode chamber, and a cathode chamber, which are separated from each other by a PTFE membrane and a three-dimensional self-supporting electrode; the anode chamber and the cathode chamber are separated by a proton exchange membrane.
[0028] Preferably, the electrolyte includes one or more of NaNO3 and KNO3, and the electrolyte further includes one or more of KOH, NaOH, Na2SO4, K2SO4, and PBS buffer.
[0029] This invention utilizes a simple electro-oxidation technique to load Cu₂O nanoneedle arrays onto a conductive substrate. Annealing effectively dehydrates and immobilizes the loaded material, and finally, simple electropolymerization modifies the polyaniline (PANI) surface. The resulting three-dimensional self-supporting electrode exhibits excellent electrocatalytic performance in the reduction of nitrate to ammonia, demonstrating high current density and high Faradaic efficiency. It is directly permeable to water and can be directly used as a key component in nitrate-to-ammonia reactors.
[0030] The non-precious metal three-dimensional electrode material prepared by this invention has a simple preparation process, low raw material cost, and strong technical versatility. No binder needs to be added later, and due to its unique self-supporting structure, the electrode material can be prepared in an integrated manner, making it highly scalable. The three-dimensional self-supporting electrode material prepared under the optimized conditions of this invention exhibits good electrocatalytic performance in the reduction of nitrate to ammonia, demonstrating excellent NO3- content. - Conversion rate and NH3 Faraday efficiency.
[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The high price of precious metals in the current market leads to high application costs, which is not conducive to the promotion and large-scale application of materials. This invention addresses the problem of over-reliance on precious metal catalysts in the field of electrocatalytic nitrate ammonia production, and prepares a high-performance catalyst using conventional transition metals (Cu) as raw materials. The non-precious metal three-dimensional electrode material of this invention has abundant metal active sites, exhibits excellent surface adsorption characteristics, and catalytic activity comparable to that of precious metals, providing a possibility for reducing the cost of large-scale application of electrocatalytic nitrate ammonia production technology.
[0032] (2) This invention develops a post-modification strategy for synthesizing polyaniline (PANI) modified Cu2O nanowire arrays, which are supported on copper foam (Cu2O@PANI / CF) as a self-supporting electrocatalyst for selective electroreduction of nitric acid to ammonia. Reasonable surface modification of the copper oxide nanowire array with polyaniline (PANI) not only preserves the structure of the nanowire array well, but more importantly, it can regulate the surface chemical microenvironment of the catalyst, accelerating electron transfer in the electrocatalytic reaction and further improving the catalytic activity of the non-noble metal three-dimensional electrode material.
[0033] (3) The method of the present invention can prepare an integrated electrode, which can be directly used as one of the components in an electrocatalytic nitrate-to-ammonia reactor. Currently, most of the catalyst materials prepared are powders, which cannot be directly used as electrodes in electrolytic cells or reactor devices. They need to be coated on carriers such as carbon paper and FTO with a binder, resulting in low loading. In addition, the contact between catalyst powders is poor, which weakens the conductivity. The electrode prepared by the present invention is a three-dimensional self-supporting structure covered by a copper oxide nanosheet array, which can be directly used as an anode and exhibits good conductivity.
[0034] (4) The process of the present invention is simple, the raw materials are inexpensive and easy to obtain. The raw materials used in the present invention and conductive substrates such as copper foam have been mass-produced, are widely available and have low costs.
[0035] (5) The three-dimensional self-supporting electrode material provided by this invention exhibits excellent performance in an electrocatalytic nitrate-to-ammonia reactor. The NH3 selectivity exceeds 80%, indicating that it can serve as a key component of the reactor to remove NO3. - It is converted into NH3 in a targeted and efficient manner. Attached Figure Description
[0036] Figure 1 The image shows a scanning electron microscope (SEM) image of the Cu2O@PANI / CF three-dimensional self-supporting electrode material obtained in Example 1.
[0037] Figure 2 This is a scanning electron microscope (SEM) image of the foamed copper electrode material precursor obtained in Comparative Example 3.
[0038] Figure 3 This is a transmission electron microscope (TEM) image of the Cu2O@PANI / CF three-dimensional self-supporting electrode material obtained in Example 1.
[0039] Figure 4 The image shows a transmission electron microscope (TEM) image of the Cu2O / CF three-dimensional self-supporting electrode precursor material obtained in Comparative Example 2.
[0040] Figure 5 The LSV linear voltammetry curves are for the electrocatalytic nitrate reduction reaction of the materials obtained in Example 1 and Comparative Example 1, respectively.
[0041] Figure 6 The EIS electrochemical impedance spectroscopy of the materials obtained in Example 1 and Comparative Example 1 for the electrocatalytic nitrate reduction reaction is shown.
[0042] Figure 7 The image shows the Faraday efficiency of the Cu2O@PANI / CF three-dimensional self-supporting electrode material obtained in Example 1 under different voltages.
[0043] Figure 8 The diagram shows the ammonia selectivity of the Cu2O@PANI / CF three-dimensional self-supporting electrode material obtained in Example 1 under different voltages.
[0044] Figure 9 This is a schematic diagram illustrating the design principle of the electrocatalytic nitrate reduction reactor of this invention. Detailed Implementation
[0045] The following examples further illustrate specific implementations of the present invention, but the implementation and protection of the present invention are not limited thereto. It should be noted that any processes not specifically described below are those that can be implemented or understood by those skilled in the art by referring to existing technology. Reagents or instruments whose manufacturers are not specified are considered to be conventional products that can be purchased commercially.
[0046] Example 1 A method for preparing a copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF includes the following steps: (1) Dissolve 120g of sodium hydroxide in 1000mL of deionized water by stirring thoroughly to obtain a 3mol / L sodium hydroxide solution.
[0047] (2) Electrodeposition was performed at room temperature. A 2cm × 1cm commercial copper foam (0.3mm thick) was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. In the sodium hydroxide solution obtained in step (1), at room temperature, at 40 mA·cm -2 Continuous oxidation with current for 600 seconds.
[0048] (3) The processed Cu(OH)2 / CF was then placed in a tube furnace, and after passing argon gas for 30 min, the temperature was increased to 300℃ at a rate of 2℃ / min and held for 2 h, and then allowed to cool naturally to room temperature. The precursor of the three-dimensional self-supporting electrode material covered by the nanoneedle array, namely Cu2O / CF, was obtained.
[0049] (4) Electropolymerization was carried out in an aniline solution. The annealed Cu₂O / CF was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. Electropolymerization was performed in a mixed solution with aniline concentration of 0.01 mol / L and sodium sulfate concentration of 0.05 mol / L at an electrode pressure of 0.5 mA·cm⁻¹. -2 Continuous oxidation with current for 500 s yielded a three-dimensional self-supporting electrode material of copper oxide nanoneedle array modified with polyaniline (PANI), namely copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF, which was directly used as one of the components in the electrocatalytic nitrate to ammonia reactor.
[0050] Comparative Example 1 By performing only steps (1), (2), and (3) of Example 1, unmodified Cu2O / CF was obtained and used for relevant electrochemical tests in the electrocatalytic nitrate ammonia production reactor.
[0051] Comparative Example 2 Only step (4) of Example 1 was performed, using a 2cm × 1cm commercial copper foam (0.3mm thick) as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. In a mixed solution with aniline concentration of 0.01mol / L and sodium sulfate concentration of 0.05mol / L, at 0.5mA·cm -2 Copper foam modified with polyaniline (PANI) surface was obtained by continuous current oxidation for 500 s, and used for related electrochemical tests in an electrocatalytic nitrate ammonia production reactor.
[0052] Comparative Example 3 A 2cm×1cm commercial copper foam (0.3mm thick) was used as the anode, a 1cm×1cm platinum mesh electrode was used as the cathode, and Ag / AgCl was used as the reference electrode for related electrochemical tests in an electrocatalytic nitrate to ammonia reactor.
[0053] Example 2 A method for preparing a copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF includes the following steps: (1) Dissolve 240g of sodium hydroxide in 1000mL of deionized water and stir thoroughly until dissolved to obtain a 6mol / L sodium hydroxide solution.
[0054] (2) Electrodeposition was performed at room temperature. A 2cm × 1cm commercial copper foam (0.3mm thick) was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. In the sodium hydroxide solution obtained in step (1), at room temperature, at 15mA·cm -2 Continuous oxidation with current for 800 seconds.
[0055] (3) The processed Cu(OH)2 / CF was then placed in a tube furnace, and after passing argon gas for 30 min, the temperature was increased to 250℃ at a rate of 2℃ / min and held for 2 h, and then allowed to cool naturally to room temperature. The precursor of the three-dimensional self-supporting electrode material covered by the nanoneedle array, namely Cu2O / CF, was obtained.
[0056] (4) Electropolymerization was carried out in an aniline solution. The annealed Cu₂O / CF was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. Electropolymerization was performed in a mixed solution with aniline concentration of 0.01 mol / L and sodium sulfate concentration of 0.05 mol / L at an electrode pressure of 0.5 mA·cm⁻¹. -2Continuous oxidation with current for 600 s yielded a three-dimensional self-supporting electrode material of copper oxide nanoneedle array modified with polyaniline (PANI), namely copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF, which was directly used as one of the components in the electrocatalytic nitrate to ammonia production reactor.
[0057] Example 3 A method for preparing a copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF includes the following steps: (1) Dissolve 120g of sodium hydroxide in 1000mL of deionized water by stirring thoroughly to obtain a 3mol / L sodium hydroxide solution.
[0058] (2) Electrodeposition was performed at room temperature. A 2cm × 1cm commercial copper foam (0.3mm thick) was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. In the sodium hydroxide solution obtained in step (1), at room temperature, at 45 mA·cm -2 Continuous oxidation with current for 600 seconds.
[0059] (3) The processed Cu(OH)2 / CF was then placed in a tube furnace, and after passing argon gas for 30 min, the temperature was increased to 280℃ at a rate of 2℃ / min and held for 2 h, and then allowed to cool naturally to room temperature. The precursor of the three-dimensional self-supporting electrode material covered by the nanoneedle array, namely Cu2O / CF, was obtained.
[0060] (4) Electropolymerization was carried out in an aniline solution. The annealed Cu₂O / CF was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. Electropolymerization was performed in a mixed solution with aniline concentration of 0.02 mol / L and sodium sulfate concentration of 0.05 mol / L at an electrode current of 0.8 mA·cm⁻¹. -2 Continuous oxidation with current for 500 s yielded a three-dimensional self-supporting electrode material of copper oxide nanoneedle array modified with polyaniline (PANI), namely copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF, which was directly used as one of the components in the electrocatalytic nitrate to ammonia reactor.
[0061] Example 4 A method for preparing a copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF includes the following steps: (1) Dissolve 400g of sodium hydroxide in 1000mL of deionized water by stirring thoroughly to obtain a 3mol / L sodium hydroxide solution.
[0062] (2) Electrodeposition was performed at room temperature. A 2cm × 1cm commercial copper foam (0.3mm thick) was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. In the sodium hydroxide solution obtained in step (1), at room temperature, at 40 mA·cm -2 Continuous oxidation with current for 300 seconds.
[0063] (3) The processed Cu(OH)2 / CF was then placed in a tube furnace, and after passing argon gas for 30 min, the temperature was increased to 350℃ at a rate of 2℃ / min and held for 2 h, and then allowed to cool naturally to room temperature. The precursor of the three-dimensional self-supporting electrode material covered by the nanoneedle array, namely Cu2O / CF, was obtained.
[0064] (4) Electropolymerization was carried out in an aniline solution. The annealed Cu₂O / CF was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. Electropolymerization was performed in a mixed solution with aniline concentration of 0.015 mol / L and sodium sulfate concentration of 0.05 mol / L at an electrode current of 0.8 mA·cm⁻¹. -2 Continuous oxidation with current for 300 s yielded a three-dimensional self-supporting electrode material of copper oxide nanoneedle array modified with polyaniline (PANI), namely copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF, which was directly used as one of the components in the electrocatalytic nitrate to ammonia production reactor.
[0065] Example 5 A method for preparing a copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF includes the following steps: (1) Dissolve 320g of sodium hydroxide in 1000mL of deionized water by stirring thoroughly to obtain an 8mol / L sodium hydroxide solution.
[0066] (2) Electrodeposition was performed at room temperature. A 2cm × 1cm commercial copper foam (0.3mm thick) was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. In the sodium hydroxide solution obtained in step (1), at room temperature, at 25mA·cm -2 Continuous oxidation with current for 1800s.
[0067] (3) The processed Cu(OH)2 / CF was then placed in a tube furnace, and after passing argon gas for 30 min, the temperature was increased to 250℃ at a rate of 2℃ / min and held for 2 h, and then allowed to cool naturally to room temperature. The precursor of the three-dimensional self-supporting electrode material covered by the nanoneedle array, namely Cu2O / CF, was obtained.
[0068] (4) Electropolymerization was carried out in an aniline solution. The annealed Cu₂O / CF was used as the anode, a 1cm × 1cm platinum mesh electrode as the cathode, and Ag / AgCl as the reference electrode. Electropolymerization was performed in a mixed solution with aniline concentration of 0.01 mol / L and sodium sulfate concentration of 0.05 mol / L at an electrode current of 0.6 mA·cm⁻¹. -2 Continuous oxidation with current for 800 s yielded a three-dimensional self-supporting electrode material of copper oxide nanoneedle array modified with polyaniline (PANI), namely copper-based three-dimensional self-supporting electrode material Cu2O@PANI / CF, which was directly used as one of the components in the electrocatalytic nitrate to ammonia reactor.
[0069] Effect verification The SEM image of the Cu2O@PANI / CF material prepared in Example 1 is shown below. Figure 1 As shown, the electro-oxidation process yields a uniformly coated three-dimensional self-supporting electrode material with a copper oxide surface modified with polyaniline (PANI) nanoneedle arrays. Furthermore, compared to the un-electro-oxidized copper foam electrode precursor in Comparative Example 3, the abundant nanoneedle arrays in the Cu2O@PANI / CF material provide a larger adsorption area and more active sites for the nitrate reduction to ammonia reaction.
[0070] TEM image of Cu2O@PANI / CF material obtained in Example 1 is shown below. Figure 3 As shown, the surface of the Cu2O / CF nanoneedles is uniformly coated with a layer of polyaniline (PANI). Compared with the Cu2O / CF electrode precursor material obtained in Comparative Example 2, the polyaniline (PANI) coating on the surface of the Cu2O@PANI / CF nanoneedles is clearly visible, and the Cu2O@PANI / CF material has stronger conductivity.
[0071] The materials obtained in Example 1 and Comparative Example 1 were used to evaluate the performance of electrocatalytic nitrate reduction reactions. Electrochemical experiments were conducted using a CHI660E electrochemical workstation from Shanghai Chenhua, employing a standard three-electrode system. The materials obtained in Example 1 and Comparative Example 1 were used as working electrodes, a 1 cm × 1 cm platinum mesh electrode as the anode, and an Ag / AgCl electrode as the reference electrode. The LSV linear voltammetry curves of the electrocatalytic nitrate reduction reactions of the materials in Example 1 and Comparative Example 1 were tested at a scan rate of 1 mV / s in an electrolyte containing 0.5 M KOH and 200 mg / L NaNO3-N. The results are as follows: Figure 5 As shown, the Cu2O@PANI / CF three-dimensional self-supporting electrode of Example 1 exhibits a high current density (-50.61 mA·cm⁻¹) at a low potential (0.1 V vs. RHE). -2 The result was significantly better than that of Cu2O / CF without polyaniline surface modification in Comparative Example 1 (-19.45 mA·cm⁻¹).-2 The reason is that polyaniline has good electrical conductivity, and the conductivity of the Cu2O@PANI / CF three-dimensional self-supporting electrode modified with polyaniline is significantly improved. At the same time, due to the presence of amino and imino functional groups, polyaniline endows the CuO surface with abundant catalytic active sites, thereby promoting NO3 catalysis. - The adsorption and hydrogenation processes. For example... Figure 5 As shown, the current density of the Cu2O@PANI / CF three-dimensional self-supporting electrode in Example 1 is much higher than that of the unmodified Cu2O / CF in Comparative Example 1, indicating that the synergistic effect of CuO and PANI can effectively improve conductivity and catalytic activity of nitric acid electroreduction.
[0072] The EIS electrochemical impedance spectroscopy of the electrocatalytic nitrate reduction reaction of the materials in Example 1 and Comparative Example 1 was tested in an electrolyte containing 0.5 M KOH and 200 mg / L NaNO3-N. The results are as follows. Figure 6 As shown, the Cu2O@PANI / CF three-dimensional self-supporting electrode of Example 1 exhibits lower impedance at low potential (-0.8V vs. Ag / AgCl), which is significantly lower than that of Cu2O / CF without polyaniline surface modification in Comparative Example 1. This is because polyaniline has good conductivity, and the electrochemical system impedance of the Cu2O@PANI / CF three-dimensional self-supporting electrode modified with polyaniline is significantly reduced.
[0073] The Cu2O@PANI / CF three-dimensional self-supporting electrode material obtained in Example 1 was used in the electrocatalytic nitrate reduction reaction. The Faradaic efficiency of the material for the reduction of nitrate to ammonia at a potential of -1.2 V vs. Ag / AgCl was calculated by detecting the concentration of ammonia species obtained after the reaction in the solution. Figure 7 As shown. Compared to other materials, the Cu2O@PANI / CF three-dimensional self-supporting electrode material provided in Example 1 of this invention has the highest Faraday efficiency (87.5%) for the reduction of nitrate to ammonia.
[0074] The Cu2O@PANI / CF three-dimensional self-supporting electrode material obtained in Example 1 was used in the electrocatalytic nitrate reduction reaction. The ammonia selectivity of the material for the reduction of nitrate to ammonia at a potential of -1.2 V vs. Ag / AgCl was calculated by detecting the concentration of ammonia species obtained after the reaction in the solution. Figure 8 As shown. Compared to other materials, the Cu2O@PANI / CF three-dimensional self-supporting electrode material provided in Example 1 of this invention has the highest ammonia selectivity (85.6%) for the reduction of nitrate to ammonia.
[0075] Combination Figures 1-8It is evident that the Cu2O@PANI / CF three-dimensional self-supporting electrode material can be effectively applied to the electrocatalytic nitrate reduction reaction. The Cu2O@PANI / CF three-dimensional self-supporting electrode material obtained in this embodiment of the invention achieves electrode integration with organic surface modification, exhibiting good conductivity and stability. By rationally controlling the parameters of point oxidation and electropolymerization, the Cu2O@PANI / CF three-dimensional self-supporting electrode material is obtained, demonstrating excellent nitrate reduction catalytic performance, exhibiting a high current density (-50.61 mA·cm⁻¹) at (0.1 V vs. RHE). -2 The electrocatalytic reduction of nitrate to ammonia achieves a Faraday efficiency of up to 87.5% and an ammonia selectivity of up to 85.6%.
[0076] Furthermore, the schematic diagram of the design principle of the electrocatalytic nitrate-to-ammonia reactor of the present invention is as follows: Figure 9 As shown, the cathode chamber and anode chamber are separated by a Nafion N117 proton exchange membrane. An acid capture chamber is added to the traditional cathode and anode chambers to transfer the electrocatalytic nitrate product NH3 from the cathode chamber to the acid capture chamber via gas diffusion. A three-dimensional self-supporting electrode and a PTFE hydrophobic and permeable membrane serve as key components of the reactor, separating the cathode chamber and the acid capture chamber.
[0077] The above embodiments are merely preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. Any changes, substitutions, modifications, etc., made by those skilled in the art without departing from the spirit and essence of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a copper-based three-dimensional self-supporting electrode material, characterized in that, Includes the following steps: (1) Using conductive three-dimensional substrate copper foam as the anode, positive voltage is applied in sodium hydroxide solution for electro-oxidation to obtain Cu(OH)2 nanoneedle array precursor electrode material; the electro-oxidation temperature is 25~50℃ and the electro-oxidation time is 300~1800s; the electro-oxidation uses platinum mesh as cathode and Ag / AgCl as reference electrode. The electro-oxidation is performed in a constant current mode, wherein the anolyte current density in the constant current mode is 15~45 mA·cm. -2 ; (2) The Cu(OH)2 nanoneedle array precursor electrode material obtained in step (1) is thoroughly immersed in pure water and then dried. It is then annealed in an inert gas atmosphere to dehydrate the precursor electrode material and obtain a precursor covered by copper oxide nanoneedle array. (3) Using the copper oxide nanoneedle array-covered precursor obtained in step (2) as the anode, positive voltage electropolymerization is applied in a mixed solution of aniline and sodium sulfate. After immersion in pure water and drying, a copper-based three-dimensional self-supporting electrode material modified with polyaniline (PANI) surface is obtained. The electropolymerization temperature is 25~50℃, and the electropolymerization time is 300~800s. The electropolymerization uses a platinum mesh as the cathode and Ag / AgCl as the reference electrode. The electropolymerization is in constant current mode, and the anode current density in constant current mode is 0.5~0.8 mA·cm. -2 .
2. The method for preparing the three-dimensional self-supporting electrode material according to claim 1, characterized in that, The concentration of the sodium hydroxide solution in step (1) is 3~8 mol / L.
3. The method for preparing the copper-based three-dimensional self-supporting electrode material according to claim 1, characterized in that, The annealing in step (2) is carried out in a tube furnace; before annealing, an inert gas needs to be introduced for 30 minutes, the annealing temperature is 250~350℃, the annealing heating rate is 2℃ / min, and the annealing time is 100~120min; the inert gas is argon.
4. The method for preparing the copper-based three-dimensional self-supporting electrode material according to claim 1, characterized in that, In step (3), the concentration of aniline in the mixed solution is 0.01~0.02 mol / L, and the concentration of sodium sulfate is 0.05~0.1 mol / L.
5. A copper-based three-dimensional self-supporting electrode material prepared by the preparation method according to any one of claims 1-4.
6. The application of the copper-based three-dimensional self-supporting electrode material according to claim 5 in the electrocatalytic nitrate reduction reaction.
7. The application of the copper-based three-dimensional self-supporting electrode material according to claim 6 in the electrocatalytic nitrate reduction reaction, characterized in that, Ammonia was synthesized by electrocatalytic reduction of nitrate using a copper-based three-dimensional self-supporting electrode material as the working electrode and a solution containing nitrate ions as the electrolyte. The reactor was designed as a three-chamber reactor, consisting of an acid capture chamber, a cathode chamber, and an anode chamber. The acid capture chamber and the cathode chamber were separated by a PTFE membrane and a copper-based three-dimensional self-supporting electrode. The anode chamber and the cathode chamber were separated by a proton exchange membrane.
8. The application of the copper-based three-dimensional self-supporting electrode material according to claim 7 in the electrocatalytic nitrate reduction reaction, characterized in that, The electrolyte includes one or more of NaNO3 and KNO3, and also includes one or more of KOH, NaOH, Na2SO4, K2SO4, and PBS buffer.
Citation Information
Patent Citations
Cu@Cu-CAT@PANI composite electrode material and preparation method and application thereof
CN111146014A
Ternary layered metal hydroxide@polyaniline composite electrode material and preparation method and application thereof
CN112542328A